2017
DOI: 10.3102/0091732x16686948
|View full text |Cite
|
Sign up to set email alerts
|

YPAR and Critical Epistemologies: Rethinking Education Research

Abstract: Knowledges from academic and professional research-based institutions have long been valued over the organic intellectualism of those who are most affected by educational and social inequities. In contrast, participatory action research (PAR) projects are collective investigations that rely on indigenous knowledge, combined with the desire to take individual and/or collective action. PAR with youth (YPAR) engages in rigorous research inquiries and represents a radical effort in education research to value the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 58 publications
(74 reference statements)
1
107
0
Order By: Relevance
“…The demonstrated benefits to youth across academic, social, and leadership domains (Anyon et al., ; Shamrova & Cummings, ) show that YPAR is a worthwhile mode of inquiry in school settings. Indeed, when grounded in YPAR's epistemological foundation, YPAR in high school settings has the potential to subvert traditional educational paradigms by legitimizing students’ experiences and knowledge (Freire, ; Caraballo et al., ). With the current review's considerations for implementation in mind, YPAR projects provide a meaningful avenue for sharing power within high school settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The demonstrated benefits to youth across academic, social, and leadership domains (Anyon et al., ; Shamrova & Cummings, ) show that YPAR is a worthwhile mode of inquiry in school settings. Indeed, when grounded in YPAR's epistemological foundation, YPAR in high school settings has the potential to subvert traditional educational paradigms by legitimizing students’ experiences and knowledge (Freire, ; Caraballo et al., ). With the current review's considerations for implementation in mind, YPAR projects provide a meaningful avenue for sharing power within high school settings.…”
Section: Discussionmentioning
confidence: 99%
“…In a review of YPAR projects to address educational inequality, Caraballo et al. () highlight similar historical roots of PAR, as well as PAR's usage with diverse multicultural and multinational origins (Mirra, Filipiak, & Garcia, ). The origins of PAR are important to understand when examining PAR projects with youth populations because it informs the implementation of such projects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using activist, liberation pedagogies within institutional spaces designed to maintain rather than challenge dominant power structures further poses practical and epistemological challenges. Caraballo et al (2017) identified four dominant entry points to YPAR, all of which, to varying degrees, inform the curriculum we describe here: (1) academic learning and literacies, (2) cultural and critical epistemologies, (3) youth development, and (4) youth organizing and civic engagement. In schools, YPAR projects risk being schoolified, its aims of inquiry and action transformed into mere graded assignments (Rubin, Ayala, & Zaal, 2017).…”
Section: Yparmentioning
confidence: 99%